Modelling the effect of factors on the stated preference towards telecommuting in IIUM campus, Gombak - Ismail, Farah Diyanah; Kadar Hamsa, Abdul Azeez; Mohamed, Mohd Zin (2016)
Objectives The increase in number of private vehicles has not only taken place in central cities, but has also occurred in university campuses. High use of private vehicles by IIUM community is posing a strain on the ability of the existing road to cope with the increasing traffic volume and parking demand within the campus. Telecommuting is one of the Transportation Demand Management (TDM) measures that aimed at reducing peak hour traffic congestion by allowing commuters to work from home to save their driving time to work, and more importantly to eliminate some vehicle trips. The main objective of this paper is to estimate the effects of the factors on the choice of telecommuting. Data and methodology Academic and administrative staff of IIUM were selected as the target population for this study because of their high involvement in using computers and internet in their daily work tasks. A total of 447 questionnaires were distributed to the employees, and of these, 300 completed questionnaires with usable data were returned, resulting in a 67.11% response rate. Two approaches were used in the data collection, namely face-to-face interviews and also through distribution of self-administered questionnaires that were later collected from the respondents. The questionnaire consists of four sections: demographic profile, trip characteristicis, work characteristics and perceptions on the aspects of telecommuting. The choice to select telecommuting is presented in an ordinal scale with three options: definitely yes; may consider; and not at all. Multinomial logistic regression was conducted to estimate the effects of socio-economic, trip and work related factors on the preference to telecommute. Expected results Parameter estimates on the administrative employees’ preference to telecommute indicate that number of young children, frequency of face-to-face communication and frequency of using email were significant factors in predicting whether an individual is more inclined to choose ‘definitely yes’ towards performing telecommuting as compared to ‘not at all’. As for academic employees, delay time (home-workplace), frequency of face-to-face communication, frequency of using fax machine, frequency of using email and frequency of using mobile network were significant predictors for the preference of ‘definitely yes’ towards telecommuting as compared to ‘not at all’.